PERAN KEPEMIMPINAN DALAM MENINGKATKAN KINERJA APARATUR SIPIL NEGARA PADA BADAN PENDIDIKAN DAN PELATIHAN KABUPATEN KUTAI TIMUR - Teresia Rani Pabetta (Jurnal Administrative Reform, 2017)
The main focus of the research includes a leadership role in improving the performance of the Civil Apparatus in Education and Training Body Kutai Timur Regency. Based on the results of the study showed that the three functions of leadership are functions that are interpersonal, role of informational, as well as the role of decision-making in general is already done by the Board of Education and Training of the Middle Kutai Regency, is indicated from various programs and activities already performed and the achievements of employees in realizing all rights and their functions in the body, so it is also an impact on improving the overall performance of the institution .